Half-metallicity and magnetism in BAs monolayer induced by anchoring 3d transition metals (TM = V, Cr and Mn). (March 2020) - Hoat, D.M.; Naseri, Mosayeb; Hieu, Nguyen N.; Ponce-Pérez, R.; Tong, Hien D.; Rivas-Silva, J.F.; Vu, Tuan V.; Cocoletzi, Gregorio H.
Abstract: The transition metals (TM = V, Cr and Mn) doping effects on the structural, electronic and magnetic properties of boron arsenide (BAs) monolayer have been comprehensively investigated using pseudopotential calculations within the framework of density functional theory (DFT). Calculations show that the pristine BAs monolayer has a graphene-like structure and its chemical bond is a mixture of covalent and ionic nature. Electronic properties results indicate that the BAs monolayer is a paramagnetic semiconductor with a direct band gap of 0.682 eV. The possibility of V-, Cr- and Mn-doping is determined by positive binding energy of 1.592, 1.668 and 1.876 eV, respectively. The incorporation of V and Cr generates the half-metallicity in the BAs monolayer with a spin-down band gap of 0.873 and 0.897 eV, respectively, while the one doped with Mn is nearly half-metallic. The doping also induces the magnetism and it is produced mainly from the 3 d orbital of the TMs with a small contribution from the nearest neighbor As atoms. Results presented in this work may be useful for the design of the magnetic nano-materials. Highlights: BAs monolayer adopts a honeycomb planar arrangement. Transition metals doping induces local structural distortion. Pristine BAs monolayer is a direct semiconductor. V- and Cr-doped BAs monolayer show half-metallicity, while Mn-doped system is nearly half-metallic. Magnetism is produced mainly from transition metal spin-up and small contribution from As spin-down.